PREVENTION OF POULTRY PASTEURELLOSIS - Nurgaliyeva Janar Sarsengalievna; Salimov Ilkhom Khaitovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. This article provides information on the prevalence, causative agent, and prevention of pasteurellosis among poultry.